Seasonal variation and heavy metal content in mangrove macroalgae from Miri estuary, Sarawak - Billah, Md. Masum (2015)
Mangrove macroalgal assemblages can be used to assess the level of bioavailable metal for environmental monitoring. To date there have been very scarce information on influence of abiotic factors on the temporal variations in occurrences and biomass production of mangrove macroalgae and their use in environmental monitoring elsewhere. Consequently, present study examined influence of some abiotic factors on the temporal changes in occurrence and biomass production of macroalgae epiphytic on pneumatophores of Avicennia marina (Forsk.) Vierh., and accumulation of heavy metal (Cu, Zn, Fe and Mn) by some of these selected macroalgae in Miri estuary, Sarawak. Within a pneumatophore two vertical segments (apex and basal) were considered to estimate frequencies of occurrences and biomass of macroalgae considering 4 seasons of Malaysia namely southwest monsoon, northeast monsoon, and two inter-monsoon. Acid extracted metals (Cu, Zn, Fe and Mn) were measured using AAS (Atomic Absorption Spectrophorometry) in surface sediment, surface water and most dominant six macroalgal species. Eleven species of mangrove macroalge were recorded, of which 6 species were common throughout the study period. From this study, macroalgal species such as Caloglossa adhaerens, , C. stipitata, C. ogasawaraensis, Bostrychia kelanensis and B. anomala were considered to be the new records in the Malaysian mangrove ecosystems. Significant differences (ANOSIM and nMDS) were observed in regards to biomass production between assemblages of two vertical segments (apex and basal) of pneumatophores. In general, marked seasonal variations were observed in the frequencies of occurrences and biomass for most of the dominant macroalgal species; presumably because of high temporal variations of hydrological and hydrochemical factors including turbidity and nutrients of the estuarine water. Canonical Correspondence Analysis (CCA) indicated that turbidity were the main variable influencing biomass production of mangrove macroalgae in Miri estuary. The scheme of metal occurrences in estuarine surface water and sediment were Fe-Mn-Zn-Cu and Fe-Zn-Mn-Cu, respectively. Among the studied metals in algal thalli; irrespective of macroalgal species the concentrations of Fe was found to be the highest, but metal having the lowest concentration varied among the species. Significant positive correlations were found between Cu-Zn in all macroalgal species (except Dictyota, sp. and C. ogasawaraensis), indicating the common origin of these elements. Concentration of each of the studied metal in thallli varied among the species, probably because of variations of thalii structure, age and growth of thalli among the species. Bioconcentrations factors (BCFs) relative to water revealed that C. leprieurii was found to be the strongest bioaccumulator for Mn, C. adhaerens for Cu and Fe and C. ogasawaraensis for Zn.